2023
DOI: 10.1177/00912174231161912
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the implementation of consultation-liaison psychiatry from the characteristics of psychosomatic consultations at a general hospital in China

Abstract: Objective To understand the current situation and characteristics of consultation-liaison psychiatry (CLP) service in general hospital, to compare the results of the literature on CLP published in other hospitals in China and abroad, and to find deficiencies for the current differences. Methods The medical records of all inpatients who had liaison consultations in the first year of the establishment of Xi'an International Medical Center Hospital, China, were collected. Statistical analysis was performed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In practice, in Chinese hospitals, the psychiatric follow-up rate of consultation patients after consultation is much lower than that of outpatients. There are few quantitative studies on CLP in China, and the reported psychiatric consultation rates (1.0 to 2.3%) are much lower than those reported abroad (2.6 to 3.3%) ( 3 ). The development of psychiatric symptoms in some patients is associated with multiple factors and requires multiple consultation sessions and psycho-behavioral treatment.…”
Section: Introductionmentioning
confidence: 93%
“…In practice, in Chinese hospitals, the psychiatric follow-up rate of consultation patients after consultation is much lower than that of outpatients. There are few quantitative studies on CLP in China, and the reported psychiatric consultation rates (1.0 to 2.3%) are much lower than those reported abroad (2.6 to 3.3%) ( 3 ). The development of psychiatric symptoms in some patients is associated with multiple factors and requires multiple consultation sessions and psycho-behavioral treatment.…”
Section: Introductionmentioning
confidence: 93%